Taxanes as a Risk Factor for Acute Adverse Reactions to Iodinated Contrast Media in Cancer Patients. (25th July 2014) - Farolfi, Alberto; Della Luna, Corradina; Ragazzini, Angela; Carretta, Elisa; Gentili, Nicola; Casadei, Carla; Aquilina, Michele; Barone, Domenico; Minguzzi, Martina; Amadori, Dino; Nanni, Oriana; Gavelli, Giampaolo
Abstract: Background: The impact of cytotoxic agents on the risk of acute allergy-like adverse reactions (ARs) to intravenous iodinated contrast media (ICM) injections is unknown. Methods: We retrospectively reviewed 13, 565 computed tomography (CT) scans performed in a consecutive cohort of cancer patients from January 1, 2010 to December 31, 2012. Episodes of acute ICM-related ARs were reported to the pharmacovigilance officer. The following matched comparisons were made: tax code, gender, primary tumor, antineoplastic therapy, and date of last cycle. Concomitant antineoplastic treatment was classified into five groups: platinum, taxane, platinum plus taxane, other, and no treatment group (no therapy had been administered in the previous 24 months). Logistic regression was used to estimate odds ratio (OR) and 95% confidence interval (CI) to evaluate the risk of acute ICM-related ARs. Results: Of 10, 472 contrast-enhanced CT scans, 97 (0.93%; 95% CI: 0.74–1.11) ICM-related ARs were reported, 11 of which (0.1%) were severe, including one fatality. The overall incidence was significantly higher in patients aged <65 years ( p = .0062) and in the platinum plus taxane and taxane groups ( p = .007), whereas no correlation was found with gender, number of previous CT scans, site of disease, or treatment setting. Multivariate analysis confirmed an increased risk for patients aged <65 years (OR: 1.73; 95% CI: 1.14–2.63) and for the taxane group (in comparison with the no treatment group; OR: 2.06; 95% CI: 1.02–4.16). Conclusion: Among cancer patients, concomitant treatment with taxanes and younger age would seem to be risk factors for ICM-related ARs. Abstract : The authors describe the incidence and impact of cytotoxic agents on the risk of acute iodinated contrast media-related adverse reactions (ARs) in a consecutive cohort of cancer patients. Results showed that such ARs are rare in cancer patients, with incidence similar to the general population. Treatment with taxanes and age <65 years seem to be risk factors.